Faktor Yang Mempengaruhi Kepatuhan Ibu Hamil Terhadap Protokol Kesehatan Covid-19 Di Puskesmas Bone-Bone Kabupaten Luwu Utara - Sarah; Andi Muh Multazam; Fatmah Afrianty Gobel (Program Pascasarjana Universitas Muslim Indonesia, 2021)
Background: Community compliance is becoming increasingly important. Efforts to build public awareness must be increased in various ways. Among other things, first, by carrying out more effective communication down to the grassroots, through various media and methods that are suitable for the diversity of ages, education and community culture / local wisdom. The purpose of this study was to analyze the factors that affect the compliance of pregnant women with the Covid 19 health protokol at Bone-Bone Health Center, North Luwu Regency. Methods: This type of research is an analytic survey with a cross sectional research design. The population in this study were all pregnant women at Bone-Bone Public Health Center, Luwu Regency, namely 180 people in March-August 2020. The sample in this study used an accidental sampling technique. Result: There is an effect of individual variables on compliance of pregnant women to health protokols and there is influence of psychological variables on compliance of pregnant women to health protokols at the bone-bone clinic in North Luwu District. Conclusion: that the variables that greatly influence, namely psychological variables, namely attitudes and motivation in pregnant women compliance with the Covid 19 health protokol at bone-bone center in North Luwu district.It is hoped that this research will provide information about the current situation of Covid-19 and increase public knowledge and awareness regarding the prevention of Covid-19 transmission in the surrounding environment, especially in pregnant women.